2019
DOI: 10.15520/ijnd.v9i05.2565
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Educational Program on Improving Nurses' Performance Regarding Arterial Blood Gases Sampling for Critically Ill Children

Abstract: Back ground:Arterial blood gases sampling is a valuable tool in the assessment of multitude of illness and injuries. It represents the criterion stander for determining a ventilated and non-ventilated children's acid base status. Aim of the study was to evaluate the effect of educational program on improving nurses' performance regarding arterial blood gases sampling for critically ill children. Setting: The study was conducted at pediatric intensive care units in Benha University hospital and Benha Specialize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 3 publications
4
5
0
Order By: Relevance
“…This result was disagree with Thulasimani, [7] who reported that none of the demographic variables were significantly associated with the level of nurses' knowledge in pretest and posttest of control group. However, the current study result was consistent with Sabaq et al, [6] that revealed a statistically significant relation between working settings, educational qualification, years of experience and studied nurses' total knowledge regarding arterial blood puncture. On the other hand, Kaur, and Charan, [26] reported that age, sex, professional qualifications, clinical experience, and working settings are related significantly with nurses' practice.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This result was disagree with Thulasimani, [7] who reported that none of the demographic variables were significantly associated with the level of nurses' knowledge in pretest and posttest of control group. However, the current study result was consistent with Sabaq et al, [6] that revealed a statistically significant relation between working settings, educational qualification, years of experience and studied nurses' total knowledge regarding arterial blood puncture. On the other hand, Kaur, and Charan, [26] reported that age, sex, professional qualifications, clinical experience, and working settings are related significantly with nurses' practice.…”
Section: Discussionsupporting
confidence: 92%
“…In this regards, the study conducted by Hemavathy et al [20] found a statistically significant difference between level of knowledge regarding arterial blood gases analysis among staff nurses before and after applying the program based learning. Moreover, consistent with the study results by Sabaq et al, [6] which reported that more than three quarter of nurses have unsatisfactory level of knowledge at the pre-program phase and the majority of them have satisfactory knowledge after program implementation about arterial blood puncture.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This study also corroborates the findings of[ 34 ] concerning the poor baseline knowledge of nurses. They found that two-thirds of nurses had insufficient practice knowledge before implementing program-based learning about arterial blood puncture, while the majority had adequate practice after implementing the program concerning learning about arterial blood puncture.…”
Section: Discussionsupporting
confidence: 92%